Sosialisasi Modifikasi Metode Transplantasi Lamun Sederhana Berbasis Sumberdaya Lokal di Pulau Kecil - Ahmad Mulyadi; Yunita Magrima Anzani; Pratita Budi Utami; Bambang Kurniadi (Fakultas Teknik, Universitas Singaperbangsa Karawang, 2025)
The degradation of seagrass meadows has prompted various efforts to restore the function and role of seagrass ecosystems in coastal areas. During two decades, various technical restoration development methods have been implemented to determine the effectiveness and efficiency of the techniques used. These methods can be adapted to the needs and conditions of the area to be restored, allowing for more flexibility in their use and implementation in the area. Lemukutan Island is a small island, approximately 45 minutes by motorized wooden boat from the main island. However, despite its relatively short distance, the island's primary economic activity is tourism, resulting in higher prices for some necessities. The 2024 DIPA PKM Agriculture Faculty program aims to introduce seagrass species, the role in the ecosystem, and implement the low-cost seagrass planting methods using the island's resources. The purpose of this community service activity is to encourage the community to participate actively in seagrass ecosystem restoration efforts.